Ultrastructural features of SARS-CoV-2 infection in the lungs - Kulhánková, Tereza (Jihočeská univerzita, 2023)
The main aim of this bachelor thesis is to investigate the ultrastructural features of SARS-CoV-2 infected lung tissues using TEM. The thesis begins with an introduction to the anatomy of the lung and the characteristics of SARS-CoV-2, including its replication process. The basic tool for this research is transmission electron microscopy (TEM), which is described here in detail, including its main components. In a separate chapter of the bachelor thesis, the sample preparation procedure and the use of the VERO cell line for the study of virus replication are described. The results of these experiments are presented and discussed with emphasis on the specific ultrastructural changes caused by SARS-CoV-2 infection. The final section summarizes the key findings and discusses their implications for our understanding of COVID-19 pathogenesis. This thesis contributes to current SARS-CoV-2 research by providing valuable insight into SARS-CoV-2 infected lung tissue at the ultrastructural level, which may aid in the development of novel therapeutic strategies against this disease.
Ultrastructural features of SARS-CoV-2 infection in the lungs
Keywords: SARS-CoV-2; virus; lungs; transmission electron microscopy; VERO cells; Covid-19; SARS-CoV-2; virus; lungs; transmission electron microscopy; VERO cells; Covid-19; immune response